Functionality and loneliness in older people: Model of mediation by positive affect - Espirito-Santo, Helena; Crúzio-Grilo, Leana; Lemos, Laura; Grasina, Alexandra; Andrade, Diogo; Daniel, Fernanda (Anales de Psicología / Annals of Psychology, 2024)
Objective: Research has shown that loneliness is associated with functional disability in the older population. However, little is known about the role of affectivity in this relationship. The present study explored a mediation model in which affectivity was hypothesized to mediate the relationship between functionality and loneliness, controlling for the effect of relevant variables. Methods: The University of California Loneliness Scale-16 items, Geriatric Functionality Scale, Positive and Negative Affect Schedule-14, and Geriatric Depression Scale-8 were administered to 489 old adults (65–100 years old), 428 from social care homes (SCH), and 61 from the community. Results: Those from SCH, women, widowed, with low education, more functional disability, more negative affect, less positive affect, and more depressive symptoms reported more loneliness. Controlling for the effect of depressive symptoms, gender, residential status, marital status, and education, only positive affect mediated, partially, the relationship between functionality and loneliness. Conclusion: We suggest implementing interventions that increase older adults’ insights in personalized patterns of positive affect and, consequently, ease feelings of loneliness in older people suffering from functional limitations (especially women, with depressive symptoms, widowed, residing in an institution, and with low educational level).